Model for generation of social network considering human mobility and interaction. (24th April 2020) - Fukae, Naoto; Miwa, Hiroyoshi; Fujihara, Akihiro
The structure of an actual network in the real world has often the scale-free property that the degree distribution follows the power law. As for a generation mechanism of a human relations network, it is necessary to consider human mobility and interactions, because, in general, a person moves around, meets another person, and makes human relations stochastically. However, there are few models considering human mobility so far. In this paper, we propose a mathematical model generating a human relations network for the purpose of fundamental research on the usage model for the utility computing. We show by the numerical experiments that a network generated by the proposed model has the scale-free property, the clustering coefficient follows the power law, and the average distance is small. This means that the proposed model can explain the mechanism generating an actual human relations network.